Evaluation of the psychological state of patients with advanced cancer and the impact of support on their emotional condition - Glińska, Jolanta; Adamska, Ewa; Lewandowska, Małgorzata; Kobos, Józef (Contemporary Oncology/Współczesna Onkologia, 2012)
The aim of the study was to evaluate the patient’s psychological state in the advanced stage of cancerous disease and to assess the effect of sustenance provided by the nursing personnel upon the emotional state of the patient. Material and methods: The study group comprised 46 subjects treated in palliative care medical wards in Łódź. The data were collected in accordance with the HADS-M questionnaire as well as a self-developed survey. The information obtained was analysed by means of Pearson χ 2 test. Results : The results obtained indicate that most subjects undergo mood aggravation. 76.2% of patients were diagnosed with depressive states. Only 19.6% of the population under investigation showed no signs of anxiety states. The study demonstrates irritation to be yet another unfavourable emotional state coupled with the advanced stage of cancerous disease with as few as 4.4% (4.2%) respondents claiming not to suffer any such symptoms. The patients highly prize the support they receive and it notably improved their well-being. Social support is essential in the advanced stage of the disease. Less severe mental disorders were noted in people who have received all kinds of support.